Fanny's dream - Buehner, Caralyn; Buehner, Mark (New York : Dial Books for Young Readers, 1996)
Fanny Agnes is a sturdy farm girl who dreams of marrying a prince, but when her fairy godmother doesn't show up, she decides on a local farmer instead.
Wilson's Children
School Library Journal starred
Notable/Best Books (A.L.A.)
2.8
K-3
Keywords: Marriage -- Fiction; Farm life -- Fiction; Marriage -- Fiction; Farm life -- Fiction